Evaluating whether stories can promote social cognition: Introducing the Social Processes and Content Entrained by Narrative (SPaCEN) framework. Issue 5 (18th August 2018) - Mar, Raymond A.
ABSTRACT: Stories have long been theorized to influence how we perceive our social world and our peers. Empirical research on this topic has begun to grow, with many studies exploring how stories and social cognition relate, across a range of different approaches. In order to structure past work and guide future investigations, this article presents a research framework that formalizes how, when, and why engagement with stories might promote social cognition. This Social Processes and Content Entrained by Narrative (SPaCEN) framework posits that stories could bolster social cognition either through (1) frequent engagement of social-cognitive processes or (2) the presentation of explicit content about social relations and the social world. These two accounts are not mutually exclusive, and both rest on different sets of necessary tenets. An example is provided to illustrate the utility of this framework, evaluating the extant work on whether exposure to stories can improve mentalizing.